Delayed and recurrent jellyfish dermatitis: A case report - Aysun Şikar Aktürk; Rebiay Kıran; Nilgün Sayman; Ayla Günlemez (Galenos Publishing House, 2024)
Jellyfish venoms cause different reactions in human skin after exposure. The most common skin findings are linear, urticarial, and painful eruptions at the areas of tentacular contact. Delayed and recurrent rashes may also occur less commonly. We report a case of a 45-year-old female patient who developed acute pruritic rash and burning as well as dizziness on the right arm while swimming off the Island of Sicily in the Mediterranean Sea. Our patient, who had an increase in lesions from time to time in the following weeks, was diagnosed with delayed and recurrent jellyfish dermatitis according to her history and clinical findings. She was treated with systemic antihistamines, systemic steroids and topical steroids. The lesions of our patient, whose lesions did not show significant improvement with systemic antihistamines, systemic steroids, or topical steroids, improved with topical tacrolimus. Since this picture is rare in our country, we found it appropriate to present our case to emphasize that jellyfish dermatitis should be kept in mind in the differential diagnosis of patients presenting with this type of skin rash and that topical tacrolimus is effective in delayed and recurrent reactions.